The plant germplasm and herbarium (WIR) collections maintained at VIR as contributors to grape genetic diversity conservation, expansion and utilization - M. M. Agakhanov; L. V. Bagmet; N. G. Tikhonova; M. V. Erastenkova; E. N. Kislin; Yu. V. Ukhatova; E. K. Khlestkina (Труды по прикладной ботанике, генетике и селекции)
Improving the standards of collecting and maintaining valuable genetic resources accessions and information about them is currently of crucial importance for the successful development of the world viticulture in the light of the challenges caused by the spread of grape diseases and climate change. This review briefly characterizes the global grapevine gene pool, approaches to its conservation, including base and duplicate conservation techniques, and the current status and prospects of the progress in in vitro and cryogenic preservation methods. The genetic potential of grape wild relatives is assessed focusing on particular species as sources of resistance genes to biotic and abiotic stressors. Achievements in the application of gene editing technologies to increase grape resistance to diseases are discussed. It is noted that a common practice at this stage is to knock out the genes responsible for grapevine susceptibility to diseases, whereas a more advantageous approach in the future will be to make targeted changes in the grape genome based on the knowledge of resistance genes in its wild relatives. Therefore, grape wild relatives need to be studied thoroughly using modern methods of forward and reverse genetics. Regarding the issues of grape genetic diversity conservation and expansion at the current technological stage, the status and significance of the plant germplasm and herbarium (WIR) collections held by VIR are scrutinized in detail. Authentication of grape germplasm accessions is marked as important, along with the role of the WIR herbarium, a unique collection incorporating physical carriers of reference genetic information on the national grapevine gene pool. Promising trends in the development of the WIR herbarium are outlined in connection with the establishment and preservation of nomenclature standards for domestic grape cultivars.